Creative integration of design thinking and strategic thinking in a design education framework - Park, Woonghee; Lee, Hyun-Kyung (Creativity Studies, 2021)
With rapid globalization, designers are increasingly required to use creative integration of strategic thinking and design thinking to deal with complexity and uncertainty in an era of constant transformation. This study reviews the current status of design education to address the key question of how strategic thinking and design thinking can be enhanced creatively in undergraduate design students’ education in South Korea. Furthermore, it investigates the key drivers for and barriers to the enhancement of strategic thinking and design thinking; seeks insights from successful design education programs; and gathers perspectives about strategic thinking and design thinking from design students, educators, and strategists. By using qualitative (in-depth interviews) and quantitative (a questionnaire) research methods, the study offers significant insights: (i) design undergraduates’ short-sighted mind-set should be reshaped, (ii) additional practical, multicultural, and interdisciplinary applications of strategic thinking are needed to bridge the gap between theoretical and practical classes, and (iii) consistent stimulation is required to internalize strategic thinking and design thinking.